SYSTEM APLIKASI PENANGANAN MASALAH LABORATORIUM PERGURUAN TINGGI RAHARJA - Fredy Susanto; Tito Herdiansah; Muhammad Romadhon (UNIVERSITAS RAHARJA, 2019)
Quite a few computer users who lack sufficient knowledge of handling hardware damage result in a computer or an institution that spends no small amount of money just to repair damage to computer hardware. Therefore the application of the damage monitoring system on the RaharjaCollege Lab computer was made to help monitor computer users in detecting damage to computer hardware along with solutions to deal with the damage. With the problem of damage to the computer Lab at Raharja College, each Laboratory consists of 5 laboratories each Laboratory computer, each class has 30 computers and a total of 150 computers. The current system is still using a manual inspection system using media laboratory computer damage checklist. Therefore, in improving maintenance services in the Lab, an application system should be developed that supports the accuracy and accuracy of the maintenance lab so that it can assist technicians in monitoring the lab, both software and hardware.